Cruise spillovers to hotels and restaurants. Issue 8 (December 2019) - Skrede, Oddne; Tveteraas, Sigbjorn Landazuri
The rapid growth of cruise tourism has spurred a debate on about spillover effects on other sectors in the port destination. In this study, we investigate the effect of cruise tourism on the demand for hotels, restaurants and cafés. We estimate a demand function for this sector applying a spatial autocorrelation regression model using panel data from Norway. The results show positive, albeit modest, demand spillover effects of cruise tourism to these onshore businesses. Policy implications and limitations of the study are discussed.